Interleukin-9 promotes cell survival and drug resistance in diffuse large B-cell lymphoma. Issue 1 (December 2016) - Lv, Xiao; Feng, Lili; Ge, Xueling; Lu, Kang; Wang, Xin
Abstract Background Interleukin-9 (IL-9) was discovered as a helper T cell growth factor. It has long been recognized as an important regulator in allergic inflammation. Recent years it was discovered to induce cell growth and differentiation of multiple transformed cells. However, its oncogenic activities in B-cell lymphomas have not been reported in detail. Methods Serum levels of IL-9 in DLBCL patients were quantified by ELISA, and its clinical significance was analysed. The expression of IL-9 receptor (IL-9R) was investigated in lymphoma cell lines by RT-PCR and western blot, respectively. In DLBCL cell lines LY1 and LY8, IL-9R genes were knocked down by RNA interference and stable transfected cells were selected with puromycin. Normal and final siIL-9R (and siControl) LY1 and LY8 cells were treated with IL-9 alone and in synergy with chemotherapeutic drugs. Cell proliferation and apoptosis were assessed by Brdu incorporation and flow cytometric analysis. The mRNA of apoptosis regulation genes were measured with real-time PCR. Results Elevated serum levels of IL-9 were detected in DLBCL patients (24/30) compared to healthy controls (0/15). Positive expression of IL-9 (defined as a serum level ≥1 pg/ml) was correlated with lower serum albumin levels and high international prognostic index (IPI) scores. IL-9R was expressed in both mRNA and protein levels in the five lymphoma cell lines, including LY1, LY8, MINO, SP53 and Jurkat. In vitro studies showed that IL-9 directly induced proliferation and inhibited apoptosis in LY1 and LY8 cells. It protects LY1 and LY8 cells from prednisolone induced apoptosis, and promotes their proliferation that were inhibited by rituximab, vincristine and prednisolone. Its molecular mechanism may be concerned with upregulating expression of p21CIP1 gene. Knock-down of IL-9R gene could reverse the effects of IL-9 on LY1 and LY8 cells. Conclusions IL-9 is associated with clinical features of DLBCL patients. It promotes survival of DLBCL cells and reduces the sensitivities of tumor cells to chemotherapeutic drugs via upregulation of p21CIP1 genes.